Time course of l‐tryptophan metabolites when fermenting natural grape musts: effect of inoculation treatments and cultivar on the occurrence of melatonin and related indolic compounds. (14th October 2018) - Fernández‐Cruz, E.; Cerezo, A.B.; Cantos‐Villar, E.; Troncoso, A.M.; García‐Parrilla, M.C.
Abstract: Background and Aims: Tryptophan is involved in the formation of bioactive compounds, such as melatonin (MEL) and 3‐indoleacetic acid (3‐IAA), by yeast. Melatonin is a neurohormone whose occurrence in wine has been widely reported in recent years. The occurrence, however, of MEL and other indolic compounds related to tryptophan metabolism by wine yeast strains has been scarcely reported in grape musts. This work examined the occurrence of these compounds during the alcoholic fermentation (AF) of musts from seven grape cultivars, Corredera, Chardonnay, Moscatel, Palomino Fino, Sauvignon Blanc, Tempranillo and Vijiriega. Methods and Results: Must was fermented with three Saccharomyces cerevisiae strains and then in two cases an additional sequential inoculation with the non‐ Saccharomyces yeast Torulaspora delbrueckii was carried out. Fermented must samples were analysed by UHPLC/HRMS to determine the concentration of:l ‐tryptophan, 5‐hydroxytryptophan, 5‐hydroxytryptamine, N ‐acetyl‐5‐hydroxytryptamine, MEL, 3‐IAA, tryptamine, tryptophol andl ‐tryptophan ethyl ester. The profile of indolic compounds during AF with the Aroma White strain depended on the cultivar. The yeast strain did not influence the profile of indolic compounds; instead, fermentation time was found to be a more influential factor. Conclusions: The production of indolic compounds during the AF depends largely on the cultivar used and the day of fermentation on natural grape musts. Significance of the Study: This is the first study that quantifies 5‐hydroxytryptophan and N ‐acetyl‐5‐hydroxytryptamine during the AF of grape must. The occurrence of compounds with bioactive potential, for example 3‐IAA and ML, during fermentation with commercial yeast strains is also described.